The Case for Absolute Spontaneity in Kant’s Critique of Pure Reason - Ellis, Addison (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Kant describes the understanding as a faculty of spontaneity. What this means is that our capacity to judge what is true is responsible for its own exercises, which is to say that we issue our judgments for ourselves. To issue our judgments for ourselves is to be self-conscious – i.e., conscious of the grounds upon which we judge. To grasp the spontaneity of the understanding, then, we must grasp the self-consciousness of the understanding. I argue that what Kant requires for explaining spontaneity is a conception of judgment as an intrinsic self-consciousness of the total unity of possible knowledge. This excludes what have been called ‘relative’ accounts of the spontaneity of the understanding, according to which our judgments are issued through a capacity fixed by external conditions. If so, then Kant conceives of understanding as entirely active. Or, to put it another way, he conceives of this capacity as absolutely spontaneous.
Keywords: Spontaneity; self-consciousness; unity; apperception; idealism